Pengaruh Penambahan Tepung Kiambang (Salvinia molesta) Terfermentasi dalam Ransum terhadap Performa Itik Peking - B T A Putro; N Nurhayati; R Noviadi (Politeknik Negeri Lampung, 2021)
The research was conducted at the Lampung State Polytechnic cage from November to December 2019. This study aims to analyze.The Effect of Adding Leaf Flour (Salvinia molesta )in the Ration on the Performance of Peking Duck. The research method is descriptive method . data collected by taking samples from P0 and P1 with a number of 40 each at the end of maintenance. data obtained were analyzed descriptively. The variables observed were ration consumption resulting in an average P0 (10,213 gr) lower than P1 (10,220 gr), body weight gain P0 (1,324.27 gr) higher than P1 (1,241.53 gr), ration conversion P0 (7,870 ) lower than P1 (8,680), mortality P0 (11%) higher than P1 (3 %)